Report on the 2024 Conference on Mechanism and Institution Design - Biró, Péter; Benedek, Márton; Ágoston, Kolos Csaba; Losonci, Dávid (Public Finance Quarterly, 2024)
The 2024 Conference on Mechanism and Institution Design (CMID) was held between 8-12 July 2024 at the Corvinus University of Budapest. The main subject of the conference is mechanism design, in general aiming at finding and analyzing the efficient and, in some sense, optimal set of rules for our social and economical systems. This wide ranging goal involves research in market design, game theory or voting, as well as behavioural economics and market competition regulations. CMID is the bi-annual conference of the Society for the Promotion of Mechanism and Institution Design, however, as opposed to the previous two iterations (in 2022 and 2022) for the first time in 6 years it was held live in person (offline), which was a great opportunity for the community to meet in person again. Accordingly it is no wonder that colleagues arrived from literally every corner of the world to present, listen and discuss the close to 300 presentations: 278 talks in 80 parallel sessions, as well as 4 outstanding plenary speakers, and 4 additional talks dedicated to celebrate Vincent Crawford’s 75th birthday made CMID a really special conference.